The Study of Critical Eco-Linguistic in Green Discourse: Prospective Eco-Linguistic Analysis - Tommi Yuniawan; Fathur Rokhman; Rustono Rustono; Hari Bakti Mardikantoro (Humaniora, 2017)
Eco-linguistic studies are influenced by one of the other interdisciplinary sciences, namely critical discourse analysis. The combination of these two sciences is called critical eco-linguistic studies. Critical eco-linguistic examines the discourse about the environment and various forms of discourse and their ideology which concerns people and the environment. The environmental discourse with all its manifestations (oral text, written text) is called green discourse. To that end, critical eco-linguistic dictates the linguistic aspects contained in the green discourse. Utilization of lingual units in green discourse will affect the sense and logic of people involved in the discourse, ie the writers and readers or the speakers and the speakers. What is recorded in their cognition, will affect their attitudes and actions to the environment. If green discourse is constructive, then their attitude and actions to the environment are constructive. Conversely, if green discourse is more destructive and exploitative, then their attitudes and actions towards the environment will also be affected towards destruction and exploitation. For this reason, critical eco-linguistic studies in green discourse deserve to be given space as a form of prospective eco-linguistic analysis.